The role of Job Engagement for Employees in ensuring customer loyalty :Applied research in a Sample of private Iraq banks - حمود العنزي, سعد علي; صبر, رنا ناصر (Journal of Economics and Administrative Sciences, 2017)
ABSTRACT      The current research aims at highlighting the role of engagement of a sample of employees who works in some of the Iraqi private banks in terms of their interaction , commitment and enthusiasm and the positive impact they own regarding their job and devote their efforts to achieve the core purpose  which is customer loyalty. The problem was expressed through a number of intellectual and practical questions.In order to achieve the aim of the research the quantitative analytical method was used depending on a questionnaire as a basic tool to collect research data and the qualitative survey method depending on semi-structured interviews which were distributed and analyzed in parallel to enhance results in the application of the current research, the targeted sample were 15 private banks working in Baghdad exclusively and the research data were collected depending on two groups of samples one of them consist of 244 manager( department managers which are in direct relationship with customers) and  branches managers, and supervisory departments. The other group of sample was the banks customers according to a questionnaire prepared specially for them and were consist of 244 customers, and the sample also include chief executive officers according to their responses in the preliminary study and the semi-structured interview.  After that data analysis was conducted and the hypothesizes were tested using appropriate statistical tools. Accordingly, it has research found that Job Engagement and Customer Loyalty are linked in a positive, which is reflected on the impact of career soundly and customer loyalty, and this is to be expected because that customer loyalty is determined by his or her customers of the quality of service and style of a good deal by the service.